Hydrodynamics Analysis in Bedono Beach Demak Regency, Central Java Indonesia : Open Resource Processing for Modeling - Rahim Mustaqim; Widyaningtias Widyaningtias; Ingerawi Sekaring Bumi; Yadi Suryadi; Eka Oktariyanto Nugroho; Hadi Kardhana; Mohammad Bagus Adityawan (Jurnal Teknik Sipil, 2022)
Abstract Input data derived from open resources is used as variables in numerical model calculation. Hydrodynamic analysis at Bedono Beach is modeled using a combination of open software models Delft3D-Flow and Delft3D-Wave. The model domain uses a combination of national bathymetry from BATNAS and national topography from DEMNAS. The driving force on this model are the tides of TPXO 7.2 and the wave results of hindcasting from National Oceanic Atmospheric and Administration (NOAA) wind data. The important water level elevation of HHWL = 1,156 m, MHWL = 1.060 m, MSL = 0.600 m, MLWL = 0.140 m, LLWL = 0,044 m are obtained from observation point on grid model. In addition, the significant wave height and significant peak period for each nautical direction are calculated and being input for open boundary in wave model. The result of one month hydrodynamic visualization after simulation complete can be seen using a quickplot menu from Delft3D. Keywords: Bedono beach, open resource, Delft3D, hydrodynamic, visualization Abstrak Data masukan yang berasal dari sumber online digunakan sebagai variabel dalam perhitungan model numerik. Analisis hidrodinamika di Pantai Bedono dimodelkan menggunakan kombinasi software Delft3D-Flow dan Delft3D-Wave. Domain model menggunakan kombinasi batimetri nasional dari BATNAS dan topografi nasional dari DEMNAS. Gaya penggera pada model yaitu pasang surut TPXO 7.2 dan gelombang hasil hindcasting dari data angin National Oceanic Atmospheric and Administration (NOAA). Elevasi muka air penting HHWL = 1,156 m, MHWL = 1,060 m, MSL = 0,600 m, MLWL = 0,140 m, LLWL = 0,044 m diperoleh dari titik pengamatan pada grid model. Selain itu, tinggi gelombang signifikan dan periode puncak signifikan untuk setiap arah laut dihitung dan menjadi masukan untuk boundary dalam model gelombang. Hasil visualisasi hidrodinamika selama satu bulan setelah simulasi selesai dapat dilihat dan dianalisa menggunakan menu quickplot dari Delft3D. Kata-kata Kunci: : Pantai Bedono, open resource, Delft3D, hidrodinamika, visualisasi